Integrating corpus linguistics into online language teacher education programs. Issue 1 (24th June 2016) - Ebrahimi, Alice; Faghih, Esmail
Abstract: This study reports on a qualitative study which explored 32 pre-service teachers' evaluations of two online seven-week introductory courses in corpus linguistics (CL). Data were gathered through questionnaires, participants' written journals, post-course semi-structured email interviews, and discussion forum entries. The qualitative analysis of data revealed that for successful integration of CL into online language teacher education programs, several procedures should be employed. These include: providing the necessary technological infrastructure in educational settings; incorporating CL instruction in initial stages of language teacher education degree programs and extending it throughout the whole curriculum; focusing more on the practical aspects of CL with much emphasis placed on the necessary pedagogical knowledge and skills for successful exploitation of CL; introducing user-friendly tools and encouraging indirect use of corpora in the absence of necessary technological facilities; providing adequate and effective instructional materials (text-based reading materials, screen capture videos, hands-on activities, etc.) along with sufficient instructor support; and encouraging the participants to reflect on the approach critically. The findings may promise implications for language teacher educators to effectively introduce CL to student teachers in virtual learning environments.